Harm reduction readiness for illicit IV drug use among safety-net primary care practices in the San Fernando Valley - Thomas Kalinoski; Cassandra DeWitt; Hrishikesh Belani (BMC, 2022)
Abstract Background Harm reduction is an accumulation of strategies aimed at preventing adverse health outcomes associated with illicit substance use. Several harm reduction programs and services exist within Los Angeles County (LAC), however their success relies in part on the application of harm reduction principles by local primary care providers serving patients with substance use disorders. This study aims to assess the readiness of patient-centered medical homes in the San Fernando Valley to provide effective harm reduction to patients who use injection drugs and identify barriers to doing so. Methods An online survey was distributed to primary care providers and social workers via email at federally qualified health centers and LAC Department of Health Services clinics in the San Fernando Valley between May and June 2019. It consisted of 22 multiple-choice, Likert scale, and short answer questions. The survey assessed knowledge of injection drug use (IDU), familiarity and utilization of harm-reduction and resources, and self-evaluation of attitudes and skills. Results There were a total of 41 survey respondents across all clinics. Of respondents, 98% correctly identified heroin as a drug typically injected, and 93% identified Hepatitis C as an infectious risk of IDU. 63% of respondents use harm reduction strategies every few months or less. 34% prescribe buprenorphine routinely, and 76% prescribe pre-exposure prophylaxis to those at risk for Human Immunodeficiency Virus (HIV). 76% are comfortable discussing IDU with their patients, but 59% indicate that they lack the necessary skills, and 42% agree that they lack the time to address it. Conclusion Knowledge of IDU was adequate among those surveyed, although overall utilization of harm reduction was infrequent. There is a perceived deficit in skills and time to effectively provide harm reduction to primary care patients in the San Fernando Valley.